Heat transfer analysis inside exhaust port for a hydrogen fueled port injection engine - Rahman, Md. Mustafizur; Hamada, Khalaf I; Abu Bakar, Rosli; Maleque, Md. Abdul (American Scientific Publishers, 2012)
This paper presents analysis of the overall heat transfer inside exhaust port for port injection hydrogen fueled internal combustion engine (H2ICE). One-dimensional gas dynamics approach was used to describe the flow and heat transfer in the components of the engine model. The engine model was executed with variable engine speed of 2000 ≤ rpm ≤ 5000 and equivalence ratio (Φ) of 0.2 ≤ Φ ≤ 1.0 and. The baseline engine model is verified with existing previous published result. The overall results show that the heat transfer characteristics increased linearly with increasing of engine speed and equivalence ratio. Finally, the investigated parameters were formulated in a new proposed correlation for heat transfer estimation inside exhaust port for H2ICE. The new proposed formula was validated by previous reliable correlation.